대학생의 이러닝 학습효과 영향요인에 대한 구조방정식 모형 연구 - 허균; Gyun Heo (Inteonet jeongbo hakoe nonmunji = Journal of Korean Society for Internet Information, 2014)
본 연구는 대학에서 이러닝을 활용 수업의 효과에 영향을 미치는 요인들을 탐색하고 요인들 간의 인과관계를 파악하고자 하였다. 이를 위해 2013년 2학기를 기준으로 이러닝 기반의 수업인 사이버 강의에 참여한 학생들 2,091명 중 유효했던 1,732명을 연구 대상으로 하였다. 연구방법은 확인적 요인분석과 구조방정식모형 분석을 활용하였다. 확인적 요인분석을 통해 이러닝 학습효과, 컨텐츠만족요인, 시스템기능요인, 운영지원요인의 네 개의 잠재변인을 도출할 수 있었다. 이들 잠재변인들 간의 구조방정식 모델 분석을 통한 결과는 다음과 같다. 첫째, 이러닝 학습효과와 관련된 주요 요인으로 컨텐츠 요인, 기능요인, 운영지원 요인으로 구분할 수 있었다. 둘째, 이러닝 학습효과에는 운영지원, 컨텐츠 요인이 직접적 영향을 미치는 것으로 나타났다. 하지만 기능요인은 유의하지 않은 것으로 나타났다. 셋째, 컨텐츠 요인에는 기능 및 운영요인이 유의한 영향을 미치는 것으로 나타났다. 넷째, 기능요인 및 운영지원 요인은 컨텐츠 요인을 매개로하여 이러닝 학습효과에 간접적 영향을 미치는 것으로 나타났다. The purpose of this study is to explore factors affecting the effect of e-learning, and to find out the casual relationship among these factors. Subjects are 2,091 students who have participated in e-learning based class during the period of second semester in 2013. Those of them, 1,732 students response to the survey questions. After gathering data, they are analyzed by using Confirmative Factor Analysis and Structural Equation Modeling. From the result of Confirmative Factor analysis, data have reduced four factors, and are named as four latent variables likes e-learning effect, contents satisfaction, managing assistant factor, and system functional factor. From the result of Structural Equation Modeling, it is known as the relation and impact among factors: (a) "managing assistant factor“ affects to ”contents satisfaction“ directly. (b) "contents satisfaction“ affects to ”e-learning effect“ directly. (c) ”system function factor“ affects directly to ”contents satisfaction“, but does not affect directly to ”e-learning effect“. (d) both "managing assistant factor“ and ”system function factor“ have an indirect effect on ”e-learning effect“ via ”contents satisfaction“.